Geriatric Specialists Prediction Based on Dynamic System Approach for the Iranian Elderly - fereshteh alizadeh; seyyed jamaledin tabibi; mohamadreza maleki; amirashkan nasiripour; abbas toloie eshlaghi (Tehran University of Medical Sciences, 2016)
Background: Demographic prediction indicates that Iran population move towards an aged society until 2025, Hence, the need for medical care will be increased.  The study aimed at predicting geriatric specialists based on dynamic system approach for the Iranian elderly. Materials and Methods: After an exploratory study, data gathering and building similar structured in order to determine geriatrics number prediction by considering the important factors. Causal loop diagram to show relationship between variables, stock-flow diagrams for quantitative analysis of system dynamic behavior was conducted and model equations in Vensim software version 5 used. Results: After simulation, intake studentschr('39') simulated model revealed increased trend then a sharp decline and finally the pattern had fixed trend from 2009 to 2012. Pattern of physician who was still in study and also graduated physician was in growing trend. Employed physician had growing trend and then it fixed, and retired physician had fixed trend at first and then had an incremental trend. Finally, the various behavior of workforce assessed in three level. Conclusion: According to increasing  growth of the elderly population until 2025,  we will encounter  with shortage  more than 2500  geriatrics which can be  compensate by 50% graduated admissions of the major annually.